2011
DOI: 10.1111/j.1469-7580.2011.01393.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of the olfactory organs in newly hatched monotremes and neonate marsupials

Abstract: Olfactory cues are thought to play a crucial role in the detection of the milk source at birth in mammals. It has been shown that a marsupial, the tammar wallaby, can detect olfactory cues from its mother's pouch at birth. This study investigates whether the main olfactory and accessory olfactory system are similarly well developed in other marsupials and monotremes at birth ⁄ hatching as in the tammar. Sections of the head of various marsupial and two monotreme species were investigated by light microscopy. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…In newborns, the development of the olfactory system varies in different species [ 70 72 ], reflecting differing developmental maturity at birth [ 70 ]. Studies indicate that in some neonate marsupials the olfactory system is capable to detect olfactory cues [ 71 73 ]. A well-developed cupula nasi at birth may provide stability in this rostral-most part of the chondrocranium (see above, [ 19 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In newborns, the development of the olfactory system varies in different species [ 70 72 ], reflecting differing developmental maturity at birth [ 70 ]. Studies indicate that in some neonate marsupials the olfactory system is capable to detect olfactory cues [ 71 73 ]. A well-developed cupula nasi at birth may provide stability in this rostral-most part of the chondrocranium (see above, [ 19 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Freyer [ 94 ] reported nerve bundles in the epithelium rostral to the cupula nasi anterior of Monodelphis domestica , possible nerves of CN V 2 that innervate the area which later develops into the rhinarium [ 108 ]. Previous studies have hypothesized a causal relation between the innervation and sensory anatomy of the area proximal to the cupula nasi anterior and the sensory biology of marsupials at birth [ 109 114 ]. Taking eye development as a reference for comparing stages, Elsner [ 115 ] observed that the cupula nasi anterior develops much earlier in Monodelphis domestica than in the tree shrew Tupaia belangeri .…”
Section: The Nasal Regionmentioning
confidence: 99%
“…Moreover, the data shown in this chapter revealed that in both dunnarts and mice neuronal production in the piriform context begins, peaks and declines earlier than the neocortex (Figure 3.2C-D). This result supports the hypothesis that the development of olfactory brain areas precedes and might influence the formation of the neocortex across mammals, and further adds to anatomical and behavioural evidence indicating that the olfactory system could be functional during the first postnatal hours, and help marsupial joeys to locate the nipples inside the pouch , Schneider 2011. The temporal definition of the generation of deeper and upper layer neurons with EdU analysis was essential to study the pattern of axonal elongation and the timeline of circuits formation, as it defined the specific stages in which it is possible to transfect and label long-range projection neurons located in L2/3 and L5 with in pouch electroporation .…”
Section: -70supporting
confidence: 84%